Nighttime and daytime dark oxidation chemistry in wildfire plumes: an observation and model analysis of FIREX-AQ aircraft data - Decker, Zachary C. J.; Robinson, Michael A.; Barsanti, Kelley C.; Bourgeois, Ilann; Coggon, Matthew M.; DiGangi, Joshua P.; Diskin, Glenn S.; Flocke, Frank M.; Franchin, Alessandro; Fredrickson, Carley D.; Gkatzelis, Georgios I.; Hall, Samuel R.; et al. (Atmospheric chemistry and physics, 2021)
Wildfires are increasing in size across the western US, leading to increases in human smoke exposure and associated negative health impacts. The impact of biomass burning (BB) smoke, including wildfires, on regional air quality depends on emissions, transport, and chemistry, including oxidation of emitted BB volatile organic compounds (BBVOCs) by the hydroxyl radical (OH), nitrate radical (NO3), and ozone (O3). During the daytime, when light penetrates the plumes, BBVOCs are oxidized mainly by O3 and OH. In contrast, at night or in optically dense plumes, BBVOCs are oxidized mainly by O3 and NO3. This work focuses on the transition between daytime and nighttime oxidation, which has significant implications for the formation of secondary pollutants and loss of nitrogen oxides (NOx=NO+NO2) and has been understudied. We present wildfire plume observations made during FIREX-AQ (Fire Influence on Regional to Global Environments and Air Quality), a field campaign involving multiple aircraft, ground, satellite, and mobile platforms that took place in the United States in the summer of 2019 to study both wildfire and agricultural burning emissions and atmospheric chemistry. We use observations from two research aircraft, the NASA DC-8 and the NOAA Twin Otter, with a detailed chemical box model, including updated phenolic mechanisms, to analyze smoke sampled during midday, sunset, and nighttime. Aircraft observations suggest a range of NO3 production rates (0.1–1.5 ppbv h−1) in plumes transported during both midday and after dark. Modeled initial instantaneous reactivity toward BBVOCs for NO3, OH, and O3 is 80.1 %, 87.7 %, and 99.6 %, respectively. Initial NO3 reactivity is 10–104 times greater than typical values in forested or urban environments, and reactions with BBVOCs account for >97 % of NO3 loss in sunlit plumes (jNO2 up to 4×10-3s-1), while conventional photochemical NO3 loss through reaction with NO and photolysis are minor pathways. Alkenes and furans are mostly oxidized by OH and O3 (11 %–43 %, 54 %–88 % for alkenes; 18 %–55 %, 39 %–76 %, for furans, respectively), but phenolic oxidation is split between NO3, O3, and OH (26 %–52 %, 22 %–43 %, 16 %–33 %, respectively). Nitrate radical oxidation accounts for 26 %–52 % of phenolic chemical loss in sunset plumes and in an optically thick plume. Nitrocatechol yields varied between 33 % and 45 %, and NO3 chemistry in BB plumes emitted late in the day is responsible for 72 %–92 % (84 % in an optically thick midday plume) of nitrocatechol formation and controls nitrophenolic formation overall. As a result, overnight nitrophenolic formation pathways account for 56 %±2 % of NOx loss by sunrise the following day. In all but one overnight plume we modeled, there was remaining NOx (13 %–57 %) and BBVOCs (8 %–72 %) at sunrise.